Comparison of the SAW (Simple Additive Weighting), AHP (Analytic Hierarchy Process) and Wieghted Product (WP) Methods in Catering Vendor Selection - Sufandi, Unggul Utan; Putri, Mayang Anglingsari; Satria Junianto, Mochamad Bagoes; Minrohayati, Minrohayati (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2025)
This study aims to develop a Decision Support System (DSS) for selecting the most suitable catering vendor for the UT Business Center by employing three decision-making methods: Simple Additive Weighting (SAW), Analytic Hierarchy Process (AHP), and Weighted Product (WP), alongside expert evaluation. Selecting an appropriate catering vendor is crucial to supporting university operations and events; therefore, the decision-making process must be based on objective and efficient criteria. Given the differences in the working principles of these three methods, it is essential to conduct a comparative analysis between AHP, SAW, and WP to determine the most suitable approach for catering vendor selection at the UT Business Center. The results of the study indicate varying levels of accuracy depending on the weighting scenario: Scenario 1 (Uniform Criterion Weights): Accuracy levels were AHP (83.33%), SAW (100%), and WP (100%). Scenario 2 (Expert-Determined Criterion Weights): Accuracy levels were AHP (58.83%), SAW (66.67%), and WP (66.67%).